1994
DOI: 10.1002/1097-0142(19940901)74:5<1595::aid-cncr2820740516>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The detection of breast carcinoma micrometastases in axillary lymph nodes by means of reverse transcriptase-polymerase chain reaction

Abstract: Background. The development of a sensitive method for the detection of breast carcinoma micrometastases in axillary lymph nodes is reported. Methods. The method was based on amplification of MUCl mRNA, which encodes a core protein of polymorphic epithelial mucin, by a reverse transcriptase‐polymerase chain reaction (RT‐PCR). Total RNA, which was extracted from a breast carcinoma cell line (MCF‐7), primary breast carcinomas, and axillary lymph nodes, was subjected to analysis of MUCl mRNA expression by the RT‐P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
131
2
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(138 citation statements)
references
References 7 publications
3
131
2
2
Order By: Relevance
“…Several reports have indicated that the detection of micrometastases using reverse transcriptase -polymerase chain reaction (RT -PCR) assay may be clinically important (Noguchi et al, 1994(Noguchi et al, , 1996Schoenheld et al, 1994;Mori et al, 1995Mori et al, , 1998Masuda et al, 2000;Manzotti et al, 2001). Moreover, screening for metastatic disease in axillary lymph nodes by RT -PCR amplification has been shown to be more sensitive and cost effective than serial sectioning and immunohistochemical staining (Lockett et al, 1998).…”
mentioning
confidence: 99%
“…Several reports have indicated that the detection of micrometastases using reverse transcriptase -polymerase chain reaction (RT -PCR) assay may be clinically important (Noguchi et al, 1994(Noguchi et al, , 1996Schoenheld et al, 1994;Mori et al, 1995Mori et al, , 1998Masuda et al, 2000;Manzotti et al, 2001). Moreover, screening for metastatic disease in axillary lymph nodes by RT -PCR amplification has been shown to be more sensitive and cost effective than serial sectioning and immunohistochemical staining (Lockett et al, 1998).…”
mentioning
confidence: 99%
“…Strategies for reducing microscopic misdiagnosis that have been tested include using immunohistochemical techniques to highlight metastases (Wells et al, 1984). More recently, a technique using reverse transcriptase-polymerase chain reaction (RT-PCR) to detect expression of tumour-associated antigen mRNA extracted from axillary nodes has been tested as an alternative to histopathological examination (Noguchi et al, 1994).However, using either serial sectioning or immunohistochemical detection in isolation ignores the alternative source of error in diagnosis. For example, in a Ludwig Breast Cancer Study Group examination of lymph nodes from 921 patients using a laborious serial sectioning procedure examining 36 sections from each block, only 9% of patients were found to have metastases [International (Ludwig) Breast Cancer Study Group, 1990].…”
mentioning
confidence: 99%
“…Strategies for reducing microscopic misdiagnosis that have been tested include using immunohistochemical techniques to highlight metastases (Wells et al, 1984). More recently, a technique using reverse transcriptase-polymerase chain reaction (RT-PCR) to detect expression of tumour-associated antigen mRNA extracted from axillary nodes has been tested as an alternative to histopathological examination (Noguchi et al, 1994).…”
mentioning
confidence: 99%
“…RT-PCR of keratin 19 (K19) transcripts has been used to detect occult breast cancer in peripheral blood and bone marrow (Datta et al, 1994). RT-PCR of MUCI mRNA, which encodes a core protein of polymorphic epithelial mucin, has been employed for the detection of micrometastases in axillary lymph nodes of breast cancer patients (Noguchi et al, 1994). In this study, we used RT-PCR amplification of PSA mRNA in peripheral blood of women with different stages of breast cancer.…”
Section: Methodsmentioning
confidence: 99%